A Review of Natural Products Against Alcoholic Liver Fibrosis - Li, Shuangjiao; Jiang, Tao; Fan, Wangdong; Liu, Peiyao; Huang, Lin (Turkish Journal of Gastroenterology, 2025)
Globally, alcoholic beverages top the charts in both sales and consumption rates. However, prolonged intake of these drinks often leads to hepatic injury, potentially progressing to more severe conditions such as hepatic fibrosis, cirrhosis, and in extreme cases, hepatocel lular carcinoma. Over the past 2 decades, pharmacological research has increasingly validated the therapeutic potential of natural botanicals and their bioactive derivatives in the clinical management of hepatic fibrosis. In this review, anti-fibrotic secondary metabo lites targeting alcohol-induced liver injury have been systematically analyzed, focusing on their botanical origins, pharmacodynamic profiles, structural characteristics, and mechanistic underpinnings. It provides some reference for developing natural products in the treatment of liver fibrosis in the future. Cite this article as: Li S, Jiang T, Fan W, Liu P, Huang L. A review of natural products against alcoholic liver fibrosis. Turk J Gastroenterol. 2025;36(8):479-487.